To whom do prior offenders pose a risk?: victim–offender similarity in police-reported violent crime - Aaltonen, Mikko (Crime & delinquency, 2017)
This study assessed whether the higher risk of victimization among criminally active and socially disadvantaged individuals is related to violent incidents including offenders with criminal backgrounds. The analysis is based on a Finnish general population sample (N = 69,635) using a 7-year-follow-up of police-reported violent incidents that enabled the measurement of criminal background of the “outside-sample” opposite parties involved in the incidents. The association between socioeconomic/criminal background and victimization grew stronger by the intensity of the criminal background of the offender. The results indicate that the risk posed by prior offenders is disproportionally targeted toward criminally active and disadvantaged individuals.